Sifat-Sifat Kuantitatif dan Jarak Genetik Kerbau Lokal Sulawesi Tenggara Berdasarkan Pendekatan Morfologi - Rusdin, Muh.; Solihin, Dedi Duryadi; Gunawan, Asep; Talib, Chalid; Sumantri, Cece (Jurnal Ilmu Pertanian Indonesia, 2018)
Information on animal genetic resource is needed in conservation program of Indonesian local buffalo. This study was aimed to analyze the quantitative traits diversity and genetic distance of local buffalo of Southeast Sulawesi local based on morphological approach. The total of 271 heads of swamp buffaloes were used in the study from four sub-populations, namely Bombana island’s, Bombana mainland, Kolaka and Konawe. Duncan Multiple Range test at 5% probability was used to compare the quantitative traits between the buffalo sub-populations. Genetic distance was analyzed by using the simple discriminant function. The results showed that the average body weight of male buffalo between sub-populations was not significantly different (P>0.05), but the average body weight of females buffalo from Bombana Island’s (465.22 ± 103.25) was significantly (P